Quality changes in depurated and undepurated green mussels (Perna viridis) at ambient storage conditions - Teruel, Sylvia Rose Luzette T.; Acevedo, Teresita P.
Undepurated and depurated green mussels (Perna viridis) were stored at ambient storage conditions. Changes in the K-value, hypoxanthine (Hx) value, trimethylamine (TMA) content, total volatile base-nitrogen (TVB-N) content, total viable count (TVC) and the number of H2S-products were monitored at regular time intervls. results were correlated with sensory and acceptability scores of the cooked green mussels. Thiobarbituric acid (TBA) value and fat content were determined at the start and end of storage. Presence of mercury, cadmium and lead was determined. Tests for the presence of coliforms and pathogenic bacteria such as Shigella, Salmonella, Vibrio cholera, Vibric parahaemolyticus and staphylococcus aureus were conducted. K-value and Hx value in both the depurated and undepurated green mussels generally fluctuated with time of storage. The TMA and the TVB-N contents were better indices in evaluating the degree of freshness of stored green mussels. TMA and TVB-N contents had significant linear relationships with time of storage. TMA and TVB-N contents of the undepurated green mussels had significant linear linear relationship with odour, flavour and acceptability scores. Significant linear relationship also existed between TMA content and flavour, and acceptability scores of the depurated green mussels. The TVC and the number of H2S-producers incresed with time of storage. The log of TVC and the log of the number of H2S-producers of the undepurated green mussels both had significant linear relationship with odour and acceptability scores. Depuration and storage had no significant effect in the TBA value and fat content of the mussels. Mercury, cadmium and lead were not removed be depuration. Depuration had little effect on the lowering of the coliforms of the mussles. Pathogenic microorganisms were not detected in the depurated and undepurated green mussles. Depurated mussels had a longer shelf-life compared to the undepurated mussels. Exposing the mussels to conditions more or less similar to the culture area during the depuration process had prolonged the shelf-life of the shellfish.
Thesis (M.S.)--University of the Philippines.
Typescript.
Keywords: Mussels; Mussels -- Storage